1995
DOI: 10.1002/bbpc.19950990410
|View full text |Cite
|
Sign up to set email alerts
|

An Optical In‐Situ Study of the Re‐Oxidation Kinetics of Calcia‐Stabilized Zirconia

Abstract: The re‐oxidation kinetics of strongly reduced single crystals of calcia‐stabilized zirconia (black CSZ) have been investigated by an optical in‐situ method at temperatures between 335 and 520°C. The kinetics obey a parabolic rate law. From the analysis of the optical results it follows that the parabolic rate constant, kp, is controlled by the ionic conductivity of the oxygen ions. The temperature dependence of kp can be represented by an Arrhenius‐type equation with an activation energy of 1.05 eV. The nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…We dismiss Zr 3+ (although several authors report on its existence in reduced stabilized zirconias, e.g., ref 19) and attribute this signal to Ti 3+ for two reasons: First, Swider and Worrell 20 and Merino et al 21 showed independently that, in reduced Ti-doped stabilized zirconia, an EPR signal with a similar g factor depends linearly on the titanium content of the samples. Second, in the reoxidation kinetics of strongly reduced zirconia, He et al 22 observed two processes exhibiting different kinetics, with the faster process being the oxidation of Zr 3+ and the slower process the oxidation of an unknown impurity, most likely Ti 3+ . Their experiments confirmed the necessity of oxygen partial pressures lower than those that can be attained with gas mixtures to reduce Zr 4+ to Zr 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…We dismiss Zr 3+ (although several authors report on its existence in reduced stabilized zirconias, e.g., ref 19) and attribute this signal to Ti 3+ for two reasons: First, Swider and Worrell 20 and Merino et al 21 showed independently that, in reduced Ti-doped stabilized zirconia, an EPR signal with a similar g factor depends linearly on the titanium content of the samples. Second, in the reoxidation kinetics of strongly reduced zirconia, He et al 22 observed two processes exhibiting different kinetics, with the faster process being the oxidation of Zr 3+ and the slower process the oxidation of an unknown impurity, most likely Ti 3+ . Their experiments confirmed the necessity of oxygen partial pressures lower than those that can be attained with gas mixtures to reduce Zr 4+ to Zr 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…Oxidation kinetics of reduced oxides following a parabolic rate law associated with color-boundary migration has been observed in numerous cases, for example, in pure and doped ZrO 2 , TiO 2 , SrTiO 3 , and Yb 3 Al 5 O 12 . [27][28][29][30][31][32] The existence of a sharp interface between the colored, reduced region and a transparent oxidized region was rationalized on the basis of oxygen activity dependence of the chemical diffusion coefficient. 27,32 A simple model for the oxidation of an N-doped TiO 2Àd thin film involving one-dimensional diffusion processes is illustrated in Fig.…”
Section: Oxidation Kinetics Of N-doped Tio 2àd Thin Filmsmentioning
confidence: 99%
“…In our simulations for Fe-doped SrTiO 3 , we assume local equilibrium, and from the known defect model 9,16 (8). Note that the way how the concentration c enters the transport coefficient in the linear equations has been developed according to linear transport theory; consequently the extension to strong deviations from equilibrium by making the transport coefficient position dependent via c(x) is not exact but only an approximation.…”
Section: Theorymentioning
confidence: 99%
“…Unfortunately, the lacking knowledge of the material's defect chemistry prevents a more detailed and quantitative analysis. This is also the case for the evaluation of the color front during oxidation of blackened zirconia (undoped ZrO 2 : Douglass and Wagner, 7 YSZ: He, Becker and Tannhauser 8 ); here the nature of the dark-colored defect is still under debate. For these systems, a parabolic rate law was shown to hold when the defect concentration (and thus oxygen potential) is about constant within the inner part of the sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation